Pengaruh Metode Latihan Ketepatan Terhadap Akurasi Lemparan Goalkeeper Cabang Olahraga Futsal (Planet Futsal Academy U-13) - Alendi, Alendi Rustam Prayoga; Hadi Kosasih, Alam; Hermawan, Irwan (Universitas Singaperbangsa Karawang, 2024)
Abstract This study employed a single group pretest-posttest design, a type of experimental research, to ascertain the impact of the accuracy training model on the accuracy of futsal goalkeeper throws. This study made use of the goalkeeper throw test tool. The population consisted of 15 individuals, while the sample consisted of 15 individuals. Saturated sampling was employed in this study due to the tiny population (less than 30 individuals). In all, 14 meetings were used in this investigation. The findings of data processing with SPSS 22 were used to determine the average pretest and posttest scores. The bowling throw (bottom) had an average pretest score of 13.93 and an average posttest score of 24.00. The overhand baseball throw had average pretest scores of 13.93 and 2.33, while the middle hip throw had average pretest scores of 13.07 and 21.93. Thus, this training regimen is appropriate for assisting Planet Futsal Academy U-13 players in increasing the accuracy of their goalkeeper throws.